2009
DOI: 10.1016/j.jneuroim.2008.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Elevated immune response in the brain of autistic patients

Abstract: This study determined immune activities in the brain of ASD patients and matched normal subjects by examining cytokines in the brain tissue. Our results showed that proinflammatory cytokines (TNF-α, IL-6 and GM-CSF), Th1 cytokine (IFN-γ) and chemokine (IL-8) were significantly increased in the brains of ASD patients compared with the controls. However the Th2 cytokines (IL-4, IL-5 and IL-10) showed no significant difference. The Th1/Th2 ratio was also significantly increased in ASD patients. Conclusion: ASD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

25
456
3
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 678 publications
(495 citation statements)
references
References 24 publications
25
456
3
11
Order By: Relevance
“…Various stimuli, such as the bacterial lipopolysaccharide (LPS) (14,17), have been shown to switch microglia into the M1 phenotype, denoted by the release of proinflammatory cytokines, interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF) (18), as well as the chemokines (C-C motif) ligand 2 (CCL2) and CCL5 (8,19), also found to be increased in brains of deceased patients with ASD. Immune dysfunction (18,(20)(21)(22) and inflammation of the brain (23)(24)(25) are now invoked in the pathogenesis of ASD.…”
mentioning
confidence: 99%
“…Various stimuli, such as the bacterial lipopolysaccharide (LPS) (14,17), have been shown to switch microglia into the M1 phenotype, denoted by the release of proinflammatory cytokines, interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF) (18), as well as the chemokines (C-C motif) ligand 2 (CCL2) and CCL5 (8,19), also found to be increased in brains of deceased patients with ASD. Immune dysfunction (18,(20)(21)(22) and inflammation of the brain (23)(24)(25) are now invoked in the pathogenesis of ASD.…”
mentioning
confidence: 99%
“…Vargas et al (2005) likewise showed the presence of an active neuroinflammatory environment, finding higher levels of MCP-1, TGF-β, and IL-6 in the brains of autistic patients. Of particular note is that many of the above studies found no increase in the Th2 cytokine IL-10 (Croonenberghs et al, 2002a;Krakowiak et al, 2015;Li et al, 2009;Molloy et al, 2006).…”
Section: Immune Dysregulationmentioning
confidence: 87%
“…The notion of a more pro-inflammatory environment was supported by Li et al (2009) who not only found elevated levels of the chemokine IL-8, pro-inflammatory cytokines IL-6, GM-CSF, and TNF-α, and the Th1 cytokine IFN-γ in autistic brain tissue, but also saw no increase in IL-4 or IL-5; as such, the authors claimed an increase in the Th1/Th2 ratio, suggesting that the Th1 arm is activated in autism.…”
Section: Immune Dysregulationmentioning
confidence: 99%
“…Injections of IgG collected from mothers of children with ASD into pregnant rhesus monkeys during the first and second trimesters led to altered brain volume and social behavior development in the offspring [75]. Analyses of post-mortem brain tissues of ASD patients with ages ranging from children to adults have revealed microglia activation and increased cytokines including TNF-α and IL-6, suggesting ongoing neuroinflammation in the brains of ASD patients [76,77]. These findings indicate that immune responses may impact on ASD pathogenesis.…”
Section: Immune Dysregulation In Asdmentioning
confidence: 99%